Ausência crônica da inervação vascular cutânea compromete a dissipação de calor durante o exercício físico - Milene Rodrigues Malheiros Lima (2011)
This study investigated the chronics effects of denervation of tail artery on the thermoregulatory adjustments induced by exercise performed in thermoneutral and warm environment. For this, were used adult Wistar rats weighting between 210-240 g at the time of first surgery. The animals were divided into two groups: submitted to denervation of theventral tail artery and submitted to sham surgery as control. The temperature sensor was implanted into intraperitoneal cavity after three weeks. After the recovery period, animals were submitted to the experimental conditions : resting in a thermoneutral environment, heatexposure, and physical exercise (18 min-1 and 5% inclination) in thermoneutral and warm environments. The chronic absence of tail artery innervation did not changed the thermoregulatory and cardiovascular parameters during the resting in thermoneutral environment, suggesting that the vascular adaptations induced by the lack of neurovascularcontrol are able to compensate for absence of the innervation. In the heat exposure, the denervated animals showed a delayed in the increase in skin temperature which, however, did not induced changes in intraperitoneal temperature. These results suggest that the fast increasein skin temperature during heat exposure is dependent of the tail artery innervation. During physical exercise, the denervated animals showed an attenuation of the increase of skin temperature and a higher increase an intraperitoneal temperature in environments, thermoneutral and warm. However, only in the warm environment was observed a reductionin performance. In addition to changes in thermoregulatory adjustments, the denervated animals showed an exacerbation of blood pressure responses to physical exercise in a thermoneutral environment. These results allow us to suggest that the absence of chronic vascular innervation alters thermoregulatory and cardiovascular adjustments induced by exercise. It is possible that the attenuation of heat dissipation has resulted in functional and structural adaptations, which may have exacerbated the increased blood pressure to trigger an increase in peripheral resistance.